Measuring the Compatibility of Conditional Decision in Formal Constitutional Review by the Constitutional Court: Menakar Kompatibilitas Putusan Bersyarat dalam Pengujian Formil Undang-Undang oleh Mahkamah Konstitusi - Rahman, Faiz; Wicaksono, Dian Agung (Constitutional Court of the Republic of Indonesia, Indonesia, 2023)
The existence of conditional decisions becomes dynamic in constitutional review, including their use in procedural constitutional reviews. Constitutional Court Decision No. 91/PUU-XVIII/2020 is the first decision to grant the petition and use a conditional decision model. Unfortunately, as mentioned earlier, using the conditional decision model in the decision results in discourse among various parties, including government institutions, law enforcers, academics, and the general public. With the growing discourse, this research aims to analyze the compatibility of the conditional decision model in formal constitutional reviews by examining various formal constitutional review decisions and the conditional decisions handed down by the Constitutional Court. This research indicates that the conditional decision is incompatible with formal constitutional review. This can be observed from the incompatibility of conditional decisions with the regulatory design of formal constitutional reviews and their legal consequences.